Studi Literatur Roadmap Pengendalian Inflasi Daerah di Indonesia - Ardila Prihadyatama; Handika Asep Kurniawan (Universitas 45 Surabaya, 2022)
This study aims to develop a roadmap for controlling regional inflation in Indonesia. The data used in this study are primary data and secondary data. Primary data in question is data sourced from interviews regarding the main tasks and functions of the Regional Inflation Control Team (TPID), while secondary data is data regarding changes in inflation in Indonesia from year to year sourced from BPS. This research method is descriptive research that utilizes literature from various related sources. The results of the study show the importance of coordination between the central government and regional governments in controlling regional inflation.